2018
DOI: 10.3389/fimmu.2018.00909
|View full text |Cite
|
Sign up to set email alerts
|

Transitional B Cells and TLR9 Responses Are Defective in Selective IgA Deficiency

Abstract: Selective IgA deficiency (IgAD) is the most common primary antibody deficiency in the western world with affected individuals suffering from an increased burden of autoimmunity, atopic diseases and infections. It has been shown that IgAD B cells can be induced with germinal center mimicking reactions to produce IgA. However, IgA is the most prevalent antibody in mucosal sites, where antigen-independent responses are important. Much interest has recently focused on the role of TLR9 in both naïve and mature B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 30 publications
1
34
2
Order By: Relevance
“…Litzman et al [52] reported that there was no significant abnormality in the B-cell subsets of IgAD patients. However, further studies indicated decreased class-switched memory B cells in SIgAD patients [11, 12]. In this line, we indicated in one study that there are 2 subgroups of patients with IgAD (group I and II) based on switched memory B cells percentage [50].…”
Section: Pathogenesis Of Sigadmentioning
confidence: 99%
See 4 more Smart Citations
“…Litzman et al [52] reported that there was no significant abnormality in the B-cell subsets of IgAD patients. However, further studies indicated decreased class-switched memory B cells in SIgAD patients [11, 12]. In this line, we indicated in one study that there are 2 subgroups of patients with IgAD (group I and II) based on switched memory B cells percentage [50].…”
Section: Pathogenesis Of Sigadmentioning
confidence: 99%
“…Few studies have evaluated the measurement of B-lymphocyte subsets in SIgAD patients [11, 12, 50-52]. Litzman et al [52] reported that there was no significant abnormality in the B-cell subsets of IgAD patients.…”
Section: Pathogenesis Of Sigadmentioning
confidence: 99%
See 3 more Smart Citations